HISTORICAL BACKGROUND AND IMPACT OF WOMEN’S INVOLVEMENT IN FORMAL EDUCATION IN NIGERIA - Ogunniyi Olayemi Jacob; Dosunmu Akinola George (European Scientific Journal, ESJ, 2014)
Girl‘s educational opportunities tend to be circumscribed by patriarchal attitude. Lack of education has been a strong visible barrier to female participation in the formal sector. The social pressures on females such as early marriage and other extraneous factors as well as consideration of female education as secondary to that of boys and certain inhibitive religious practices are the major causes of the high illiteracy rate amongst women. As the impact of teenage pregnancy and early marriage make abundantly clear, girls are at a double disadvantage in educational access especially in the Northern part of the country where these practice are mostly widespread. Parents attach greater importance to the education of boys than girls. This is always the likelihood when the parents lack resources to enrol all children in school. In some families, investing in girl‘s education is regarded as investing for the benefit of the family she will eventually marry into. This argument holds in particular for higher education, which involves greater expenditure and is seen to be less necessary for female. This paper through the use of secondary sources attempt the historical background of women‘s education in Nigeria, which later led to their involvement in formal education sector bringing to an end female inferiority complex established from childhood through social interactions in the home.